PENGARUH METODE PEMBELAJARAN KOLABORATIF TERHADAP KETERAMPILAN KEPEMIMPINAN DI PERGURUAN TINGGI ISLAM: PERAN MOTIVASI INTRINSIK DAN EKSTRINSIK SEBAGAI FAKTOR MEDIASI - Arifin, Muhammad; Abidin, Munirul (Idaarah: Jurnal Manajemen Pendidikan, 2025)
Nowadays, leadership is an important indicator in solving problems. However, some students in tertiary institutions are still not motivated to recognize the the importance of leadership in learning. The application of collaborative collaborative learning method is a first step to be able to achieve leadership skills. leadership skills, the problem is that most students do not understand the concept of the method towards leadership. the concept of the method towards leadership. So, the purpose of this study of this study is to determine the effect of collaborative learning methods on leadership skills of leadership skills mediated by intrinsic and extrinsic motivation. extrinsic motivation. This research was conducted with a quantitative approach using random sampling technique distributed via WhatsApp messages from several students of Islamic universities in Malang city by filling out a questionnaire on googleform. filling out a questionnaire on googleform. Data collected as many as 100 respondents and analyzed using SmartPLS 4. The results showed that collaborative learning has a significant effect on leadership skills. Collaborative learning has a significant effect on leadership skills. Collaborative learning has a significant effect on the role of intrinsic and extrinsic motivation. intrinsic and extrinsic motivation and intrinsic and extrinsic motivation mediate the relationship between collaborative learning and leadership skills. mediate the relationship between collaborative learning and leadership skills.